Quasi-one dimensional classical fluids - Percus, J.K.; Wang, Q.-H. (Condensed Matter Physics, 2003)
We study the equilibrium statistical mechanics of simple fluids in narrow pores. A systematic expansion is made about a one-dimensional limit of this system. It starts with a density functional, constructed from projected densities, which depends upon projected one and two-body potentials. The nature of higher order corrections is discussed Ми вивчаємо рівноважну статистичну механіку простого плину в обмежених порах. Систематичне розвинення виконане в одновимірній границі цієї системи, яке базується на функціоналі густини, по- будованому з проектованих густин, що залежать від одно- і дво-частинкових потенціалів. Обговорюється природа кореляцій вищих порядків.